Prenatal predictors of motor function in children with open spina bifida: a retrospective cohort study. (4th November 2020) - Corroenne, R; Yepez, M; Pyarali, M; Johnson, RM; Whitehead, WE; Castillo, HA; Castillo, J; Mehollin‐Ray, AR; Espinoza, J; Shamshirsaz, AA; Nassr, AA; Belfort, MA; et al.
Abstract : Objective: To identify predictors for intact motor function (MF) at birth and at 12 months of life in babies with prenatally versus postnatally repaired open spina bifida (OSB). Design: Retrospective cohort study. Setting: Texas Children's Hospital, 2011–2018. Population: Patients who underwent either prenatal or postnatal OSB repair. Methods: Prenatal MF of the lower extremities was evaluated by ultrasound following a metameric distribution at the time of diagnosis (US1), 6 weeks postoperatively (or 6 weeks after initial evaluation in postnatally repaired cases) (US2) and at the last ultrasound before delivery (US3). At birth and at 12 months, MF was assessed clinically. Intact MF (S1) was defined as the observation of plantar flexion of the ankle. Results from logistic regression analysis are expressed as odds ratios (95% confidence intervals, P values). Results: A total of 127 patients were included: 93 with prenatal repair (51 fetoscopic; 42 open hysterotomy repair) and 34 with postnatal repair. In the prenatal repair group, predictors for intact MF at birth and at 12 months included: absence of clubfeet (OR 11.3, 95% CI 3.2–39.1, P  < 0.01; OR 10.8 95% CI 2.4–47.6, P  < 0.01); intact MF at US1 (OR 19.7, 95% CI 5.0–76.9, P  < 0.01; OR 8.7, 95% CI 2.0–38.7, P  < 0.01); intact MF at US2 (OR 22, 95% CI 6.5–74.2, P  < 0.01; OR 13.5, 95% 3.0–61.4, P  < 0.01); intact MF at US3 (OR 13.7, 95% CI 3.4–55.9, P  < 0.01; OR 12.6, 95% CI 2.5–64.3, P  < 0.01); and having a flat lesion (OR 11.2, 95% CI 2.4–51.1, P  < 0.01; OR 4.1, 95% CI 1.1–16.5, P  = 0.04). In the postnatal repair group, the only predictor of intact MF at 12 months was having intact MF at birth (OR 15.2, 95% CI 2.0–113.3, P  = 0.03). Conclusions: The detection of intact MF in utero from mid‐gestation to delivery predicts intact MF at birth and at 12 months in babies who undergo prenatal OSB repair. Tweetable abstract: Detection of intact motor function in utero predicts intact motor function at birth and at 1 year in fetuses who undergo prenatal OSB repair. Tweetable abstract: Detection of intact motor function in utero predicts intact motor function at birth and at 1 year in fetuses who undergo prenatal OSB repair.